2022
DOI: 10.1021/acsmaterialslett.2c00091
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ionic Liquids and Derived Materials to High-Efficiency and Stable Perovskite Solar Cells

Abstract: Metal halide perovskite solar cells (PSCs) are emerging photovoltaic technology that have attracted worldwide attention owing to their potential to disrupt the established market of silicon solar cells. Despite much effort, several lingering issues, such as device efficiency and stability, are still needed to be solved for the commercial application. Ionic liquids with unique properties, such as high ionic conductivity, good thermal stability, and chemical designability, have shown to play multiple functions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 178 publications
0
36
0
Order By: Relevance
“…Room temperature ionic liquid (RTIL) has been of interest in broad scientific fields owing to its specific natures that are attainable by neither ionic solids nor organic liquids. [1][2][3][4] The history of RTIL began with finding ethyl-primary-ammonium nitrate (CH3CH2NH3NO3; m.p. = 285 K) in 1914 (Figure 1a; left), 5 and thus, aliphatic-primary-ammonium is the architype cation of RTIL.…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature ionic liquid (RTIL) has been of interest in broad scientific fields owing to its specific natures that are attainable by neither ionic solids nor organic liquids. [1][2][3][4] The history of RTIL began with finding ethyl-primary-ammonium nitrate (CH3CH2NH3NO3; m.p. = 285 K) in 1914 (Figure 1a; left), 5 and thus, aliphatic-primary-ammonium is the architype cation of RTIL.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskites have emerged as a versatile and prominent semiconductor for solution-processable electronics . By employing perovskites as active layers, solar cells and light-emitting diodes have recorded power convention efficiencies exceeding 25% and external quantum efficiencies over 25%. Perovskites have also shown notable performances in memory and neuromorphic devices. These remarkable achievements have been established based on the exceptional material properties of perovskites, such as large absorption coefficients, high dielectric constants, long carrier diffusion lengths, and low exciton binding energies. Another notable advantage of perovskites is their high charge carrier mobility surpassing that of the conventional processable semiconductors such as organic semiconductors, amorphous silicon, and indium gallium zinc oxide (IGZO). From Hall effect, optical-pump-THz-probe, space charge limited current, and time-of-flight measurements, the mobility of perovskite semiconductors have been estimated to be over 100 cm 2 V –1 s –1 . Accordingly, perovskite transistors have also been investigated accompanied by strategic approaches such as compositional tuning, morphology optimization, contact modification, and defect engineering. As a pioneer work, Kagan et al demonstrated a hole mobility of ∼0.6 cm 2 V –1 s –1 using a two-dimensional layered perovskite composed of organic phenethylamine and inorganic tin iodide …”
mentioning
confidence: 99%
“…We ascribe this to the formation of perovskite-OEG complex that contributes to the trap passivation on the perovskite surface. , Accordingly, the different passivation abilities of the OEG groups depending on side-chain length were investigated by performing photoluminescence (PL) analysis. Steady-state PL spectra of the perovskite films treated with MM or ML monomers with medium and long OEG side chains show a hypsochromic shift in emission peaks (2 nm) compared with the pristine film and perovskite film treated with the MS with short OEG side chains (Figure b).…”
mentioning
confidence: 99%
“…Unparalleled progress in metal-halide perovskite photovoltaics (PPVs) with reported certified power conversion efficiencies (PCEs) of over 25% under AM 1.5G solar radiation has recently been reported. This impressive feat has been attained primarily through the composition and fabrication method of the perovskite photoactive layer. Concomitantly, the advent of functional layers for optimizing the interfaces within PPVs has been a pivotal milestone in their development. These layers facilitate charge transport, block unwanted charge carriers, and enhance interaction between the neighboring layers, thereby boosting the PCE of the PPV. Specifically, organic hole transport materials (HTMs) and their π-conjugated moieties have been designed to realize desirable electrical properties in the PPV, such as appropriate energy level alignment for reducing the energy loss during hole extraction and effective charge percolation as a result of molecular packing to enhance the delivery of hole carriers. The recent design roadmap for HTMs has been extended to embed functionality by using side groups.…”
mentioning
confidence: 99%